Republic of Niger : Towards an Integrated and Sustainable Pension System - World Bank (Washington, DC, 2014)
This report was prepared at the request of the Government of Niger to: (i) provide a comprehensive assessment of the Nigerien pension system, (ii) analyze current reform initiatives and recommend possible refinements and alternatives, and (iii) examine implementation challenges. To this end, the report develops a set of general guidelines to assess reform options in terms the adequacy of benefits, security, financial sustainability, redistribution, incentives, and administrative efficiency. The core of the report is organized in three chapters. After providing a summary of the background (chapter one), chapter two develops the policy framework and updates the assessment of the mandatory pension systems. The assessment looks at the financial situation of the schemes but also discusses other problems that had been previously overlooked in terms of the adequacy of benefits; the type of redistribution; as well as issues related to incentives. Chapter three reviews Government ongoing reform initiatives, summarizes the international experiences that are relevant to Niger, and, presents recommendations to strengthen current policies by outlining the components of a multi-year reform program, and developing a road map towards implementation.